RPJPN 2025-2045: Women as Subject or Object of Development ? - Dwi Rahayu Nurmiati (Universitas Sultan Ageng Tirtayasa, 2025)
Gender equality is prominently featured in Indonesia’s National Long-Term Development Plan (RPJPN) 2025–2045 as part of its commitment to inclusive development. However, the integration of gender perspectives across development sectors remains largely normative, lacking a clear framework for empowering women as active agents rather than passive recipients. The gap between rhetoric and practice raises concerns about whether national development planning can effectively contribute to structural gender transformation. To explore this issue, a qualitative literature review was conducted, drawing on academic publications, policy documents, and institutional reports from 2015 to 2025. Longwe’s Gender Analysis Framework consisting of five levels: welfare, access, conscientization, participation, and control was employed to assess how the RPJPN addresses various dimensions of women’s empowerment. The analysis reveals that while the RPJPN expands women’s access to education, health, and economic programs, it falls short in promoting critical awareness, institutional participation, and control over resources and decision making. Structural barriers, including patriarchal norms, limited ownership rights, and lack of gender-responsive governance, remain largely unchallenged. The findings indicate that the RPJPN offers inclusion without empowerment. Without embedding mechanisms for redistributing power and transforming institutional cultures, gender mainstreaming efforts risk remaining symbolic, failing to achieve the transformative change necessary for long-term gender equality.